History of examination and source study analysis of Amir Timur’s diploma issued by the Turkestan mosque of Khoja Ahmet Yasavi at the end of the XIV-beginning of the XV century - Kartova, Z.K. (KSU publ., 2019)
The article is devoted to a source study of the form of the waqf certificate issued by Amir Timur of the Turkestan mosque of Khoja Ahmet Yasavi in the late XIV — early XV centuries. This is one of the earliest documents related to the socio-economic history of the cities of southern Kazakhstan. For a long time, the letter was considered a fake document. At the same time, the analysis of the form and steady turnovers applied to medieval acts of sources makes it possible to question the falsity of this document. It is determined that the conditional form of the waqfic literacy corresponds to all the structural components of medieval labels that were widely used in the chancellery of the Golden Horde and post-Golden Horde states. Diplomatic analysis of the document form confirms that all the articles of the initial label protocol (invocation, intitulation, inscription) are present in the amir of Amir Timur. In the main part of the document, which consists of notification, sanction and corroboration, there are all the elements of the waqf (soyurgal) label. The final protocol (eschatocol) is missing. The order of their arrangement corresponds to the form of the granted labels issued during the period of functioning of the post-Golden Horde states. It should be taken into account that the publication of the waqfic diploma issued by Amir Timur to the Turkestan mosque of Khoja Ahmet Yasavi at the end of the XIV — beginning of the XV centuries is of great importance for historical science. The source can be used in scientific research as the most important autochthonous and authentic source of the Middle Ages, containing genuine information about the socio-economic history, forms of land ownership and religious life of the medieval cities of southern Kazakhstan.
Keywords: waqfic literacy; conditional form; source study; Khan's label; medieval source